Penerapan Experiential Learning dalam Pengembangan Kompetensi Sosial Emosional Peserta Didik - Safia Safitri (LPPI Yayasan Almahmudi bin Dahlan, 2025)
This research is a literature review that aims to explore the application of experiential learning approach in developing learners' social-emotional competence. The background of this study is based on the increasing need for learning strategies that not only develop cognitive aspects, but also support learners' emotional and social growth holistically. The method used in this review is narrative synthesis and thematic analysis of relevant literature selected through certain inclusion criteria, such as publication within the last 10 years and focus on primary to secondary education. The results of the literature review show that the application of experiential learning has a significant influence on the development of learners' social-emotional competence. Three main themes emerged through thematic analysis: first, direct experience as the foundation of emotional learning; second, the role of reflection in shaping self-awareness and emotion regulation; and third, the importance of collaborative social contexts in fostering empathy and interpersonal skills. It is hoped that the results of this study can serve as a reference for pre-educators in designing more effective learning to increase students' independence.